014 Shared decision making: T-MACS choice for chest pain patients in the ED. Issue 12 (21st November 2019) - Ward, Abigail; Berg, Patricia van den; Body, Richard
Abstract : The concept of shared decision making (SDM) has gained increasing attention across healthcare fields including emergency care, with a focus shift towards patient-centred medicine. With cardiac chest pain accounting for approximately 6% of all emergency department (ED) attendances we aimed to co-design a personalised decision aid based on the established Troponin-only Manchester Acute Coronary Syndromes (T-MACS) prediction model to increase patient involvement in the decision making on serial troponin testing and follow up. The T-MACS Choice decision aid was co-designed with patient and physician involvement in 7 stages using a mixed-methods approach (figure 1 ) at the Manchester Royal Infirmary (MRI) from March to May 2017. The initial prototype was developed based on a) a literature review of SDM, b) the AHRQ health literacy toolkit and c) the International Patient Decision Aid Standards instrument. In subsequent stages the prototype was improved based on feedback provided by the PRIMER patient and public involvement group, three SDM expert clinicians, focus groups interviews involving 26 members from patient groups with a history of cardiac problems, questionnaires from 29 emergency physicians and 14 patients presenting to MRI ED with chest pain and admitted for serial troponin testing. The final T-MACS Choice decision aid is personalised for the individual patient, reflecting their distinct risk group with the relevant choice options (figure 2 ). In the initial development stages the most common themes identified were the importance of a personalised design and the use of clear, understandable language avoiding medical jargon. Both patients and physicians highlighted the importance of including information on heart health and prevention. In the final stages both sides agreed that T-MACS Choice had the right amount of information, was clear and engaging patients in the decision making. Further research on clinical implementation of T-MACS Choice is needed to determine its impact on patient choice and safety.